2017
DOI: 10.3389/fncel.2017.00205
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Extracellular Vesicles Ameliorates Hippocampal Synaptic Impairment after Transient Global Ischemia

Abstract: Recent studies have found that administration of stem cells or extracellular vehicles (EVs) derived from stem cells exert neuroprotective effects after transient global ischemia. However, the underlying mechanisms of this effect remain unclear, especially at the level of synaptic functions. In this study, we compared the suppressive effects on cyclooxygenase-2 (COX-2) upregulation by EVs derived from bone marrow mesenchymal stem cells (BMSC-EV), adipose tissue MSC (AdMSC-EV) and serum (serum-EV). Then we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…BMSCs have been widely investigated because of their therapeutic potential in various diseases such as nervous system diseases and autoimmune diseases (13,(30)(31)(32)(33). Recently, the use of BMSCs in renal I/R injury therapies has generated interest; nevertheless, the therapeutic features and underlying mechanisms remain elusive and need to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMSCs have been widely investigated because of their therapeutic potential in various diseases such as nervous system diseases and autoimmune diseases (13,(30)(31)(32)(33). Recently, the use of BMSCs in renal I/R injury therapies has generated interest; nevertheless, the therapeutic features and underlying mechanisms remain elusive and need to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the therapeutic effects of BMSCs were a result of their differentiation potential; however, reports have increasingly suggested that the functions of BMSCs might be attributable to potent paracrine activities such as cytoprotective factors and exosomes (15,32,35,36). A series of cytoprotective factors secreted by BMSCs have been demonstrated to play the important mediatory function of BMSCs (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Since MSC-derived EVs are also able to ameliorate hippocampal synaptic impairment after ischemia [303] as well as memory dysfunction after status epilepticus [304], these vesicles are at the moment the object of much research aimed at finding out new therapies for brain injury and malfunction.…”
Section: Natural As Well As Engineered Evs As Drug Carriersmentioning
confidence: 99%
“…MSC-EVs have also been reported to reduce the hepatic injury by improving the hepatocytes viability, suppressing oxidative injury and modulating the inflammatory response in vivo [10]. MSCs-derived EVs were also successfully applied to treat transient global ischemia in mice, where the neuroprotective effects of MSC-EVs were demonstrated [11]. Based on these findings, the cell-free therapy concept was developed, where the MSCs-derived EVs are used instead of cells [12][13][14].…”
Section: Introductionmentioning
confidence: 99%